Update on Ozone-Depleting Substances (ODSs) and Other Gases of Interest to the Montreal Protocol - Engel, A. (2019)
This chapter concerns atmospheric changes in ozone-depleting substances (ODSs), such as chlorofluorocarbons (CFCs), halons, chlorinated solvents (e.g., CCl 4 and CH 3 CCl 3 ) and hydrochlorofluorocarbons (HCFCs), which are controlled under the Montreal Protocol. Furthermore, the chapter updates information about ODSs not controlled under the Protocol, such as methyl chloride (CH 3 Cl) and very short-lived substances (VSLSs). In addition to depleting stratospheric ozone, many ODSs are potent greenhouse gases. Mole fractions of ODSs and other species are primarily measured close to the surface by global or regional monitoring networks. The surface data can be used to approximate a mole fraction representative of the global or hemispheric tropospheric abundance. Changes in the tropospheric abundance of an ODS result from a difference between the rate of emissions into the atmosphere and the rate of removal from it. For gases that are primarily anthropogenic in origin, the difference between northern and southern hemispheric mole fractions is related to the global emission rate because these sources are concentrated in the northern hemisphere.